Beyond the Digital Divide: The Effectiveness of Mind Mapping in Arabic Vocabulary Learning in Resource-Limited Madrasahs - Sari Khusna Nabila; Anyes Lathifatul Insaniyah (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
The digital divide has limited technology-based instruction in many madrasahs, leading to continued reliance on rote learning for Arabic vocabulary memorization. This study examines the effectiveness of mind mapping as a low-technology strategy to improve Arabic vocabulary retention in a resource-limited madrasah context. A quasi-experimental nonequivalent control group pretest–posttest design was used involving 50 tenth-grade students divided into experimental and control groups. Data were collected using a 30-item multiple-choice test and analyzed using descriptive statistics, Shapiro–Wilk and Levene tests, independent samples t-test, and N-Gain analysis. The results showed that the experimental group achieved higher posttest scores (M = 87.48) than the control group (M = 64.68), with a significant difference (p < .001) and a large effect size (d = 2.50). The N-Gain score indicated greater improvement in the experimental group (73.96%) compared to the control group (16.77%). These findings demonstrate that mind mapping is an effective, context-sensitive strategy for enhancing Arabic vocabulary memorization. The study provides evidence from a resource-constrained context and challenges the assumption that learning effectiveness depends on digital technologies. It highlights cognitive organization as a key factor in vocabulary learning and recommends its adoption in similar educational settings.